2015
DOI: 10.1097/qai.0000000000000433
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Stress and the Mediating Role of Alcohol Use on HIV-Related Sexual Risk Behavior

Abstract: Background In South Africa, alcohol contributes to the HIV epidemic, in part, by influencing sexual behaviors. For some, high levels of alcohol consumption may be driven by previous traumatic experiences that result in traumatic stress. The purpose of this study was to quantify the longitudinal association between traumatic stress and unprotected sex among women who attend drinking venues and to assess whether this association was explained by mediation through alcohol use. Methods Data were collected in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Condom use also declines in the context of alcohol or other substance use [105]. For women, alcohol use may increase during the transition to adulthood, in response to life stressors, including pregnancy, or with exposure to adults with heavier drinking behaviors [40,41,105]. Structural and community level interventions have an important role to play in increasing condom use [104].…”
Section: Sexual Risk Behaviorsmentioning
confidence: 99%
“…Condom use also declines in the context of alcohol or other substance use [105]. For women, alcohol use may increase during the transition to adulthood, in response to life stressors, including pregnancy, or with exposure to adults with heavier drinking behaviors [40,41,105]. Structural and community level interventions have an important role to play in increasing condom use [104].…”
Section: Sexual Risk Behaviorsmentioning
confidence: 99%
“…Risky drinking was found to be a significant predictor of RSB. This finding adds to a growing body of research indicating a strong link between alcohol and sexual risk behaviour [19], especially when drinking occurs during sexual events [5,65]. The use of alcohol explains 23.22% of the variance in RSB.…”
Section: Discussionmentioning
confidence: 53%
“…A number of explanations could potentially account for this; however, the most notable is the stigma attached to reporting sexual activity and alcohol use. According to South African women's drinking patterns, 24% report alcohol use, and those who do drink tend to drink hazardously [65]. In South Africa, women's drinking habits have remained consistent over time, with little evidence of a decline.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research from Malawi and the region point to several potential reasons why these gaps between the three groups exist and where interventions may be targeted to achieve greater impact. Numerous studies have shown that women who frequent alcohol serving venues, like OFSW and OHRW, have an increased prevalence of psychosocial factors that can exacerbate HIV infection risk [14][15][16][17][18][19][20][21]. One study in South Africa found women who attended alcoholserving venues daily had more partners and more unprotected sex than those who didn't [22].…”
Section: Discussionmentioning
confidence: 99%